Review on Friction Compensation Approach For Machine Tools Application - Rafan, Nur Aidawaty; Jamaludin, Zamberi; Abdullah, Lokman; Chiew, Tsung Heng; Mat Ali, Mahasan (2012)
This paper reviews a basic understanding on importance of friction compensation in machine tools application. More often, the difficulty in compensation appears in position and tracking error, more specifically referred to as quadrant glitches. Friction, a nonlinear phenomenon is compensated using various techniques; model based and non-model based. This paper discusses the advantages and limitations of model and non-model based. Recently, friction compensation is focusing in designing friction compensation method that adapt changes within the system.